As trilhas sociais da escrita de si na ficção de Alina Paim - Maciel, Luciana Novais (2024)
This thesis defends the hypothesis that the "writing of the self" is one of the characteristics of Alina Paim's resistance to the Brazilian Communist Party (PCB) demands for a socialist literature. We verify this premise based on Alina Paim's novels Estrada da liberdade (1944), Simão Dias (1949) and Sol do meio-dia (1961), by checking the construction of the plots and characters, seeking to clarify the relationship between the author's memories, the challenges faced by the characters and the writer's trajectory in the process of elaborating the narratives. We therefore argue that the novels analyzed incorporate memories of her experiences with writing and her political engagement through a textual and social construction, which privileges a particular feminine universe, proper to "writing of the self", as it focuses on the challenges of women in a patriarchal and capitalist society. We looked at how this writing was worked on in Paim's text, starting with Estrada da liberdade and being taken up and reworked in Sol do meio-dia, unfolding from the protagonist writer. Through this research, we seek to contribute to bringing Alina Paim to the light of historiography, since her writings have been recognized through national awards, the translation of two novels into Bulgarian and Russian, and the writer's constant presence in literary spaces, always present in weekly literature journals since her debut. Between her writings, we see the strong influence of her political activism, also represented through her characters, her speeches, the readings commented on in her novels, and her critical approach to the relationship between the oppressors and the oppressed. We reflect on the engagement of the intellectual, who as an artist seeks to write her authentic self in the novels. In order to prepare this thesis, we sought to draw on the following researchers and their respective conceptualizations. With regard to women's studies, we took Constância Lima Duarte (2003), Elódia Xavier (2012), Ana Leal Cardoso (2009, 2019) and Iracélli Alves (2015), among others, as our theoretical contribution. With regard to the discussion about the engagement of the intellectual's authorship, we take as our theoretical basis the studies of Edward Said (2005), Michel Foucault (2004) and Jean-Paul Sartre (1948). We refer to the study of autofiction and the writing of the self based on the studies of Philippe Lejeune (2008), Eurídice Figueiredo (2007), Margareth Rago (2000). The thesis is organized into four chapters, the first of which discusses the social context and the role of the intellectual in the face of social realism. In the second chapter, we look at ideological reception, based on the critical fortune, the reach of the literary sections of various newspapers and some of the prefaces contained in the novels analyzed. In the third, we discuss the resistance of intimate writing, the place of the intellectual through "writing of the self". In the fourth chapter, we develop the path of "writing of the self", observing the place of engaged writing and the work of the intellectual. In this sense, we refer to the analysis and insertion of Alina Paim's novels in the perspective of the historiography of Brazilian literature.